Contribution Analysis of the Leading Sector; Using Location Quotient Method and Klassen Typology - Firdaus, Wahyu Tri Nur Ahmad (AIBPM Publisher, 2023)
Regional economic development has an important role in the national economy, because it is part of creating superior quality resources to determine the direction of the economy. This study aims to determine the basic and non-basic sectors with the calculation of Location Quotion (LQ) and quadrant type in the typology of the economy of Batang Regency, Central Java Province from 2011 to 2018 seen based on Gross Regional Domestic Product to see what sectors are superior and not superior. The type of research uses secondary data from the publication of the Central Statistics Agency (BPS) of Batang and Central Java, with quantitative methods. The results of the study show that there are 9 basic sectors and 7 non-basic sectors from 2011 to 2018, with a slight difference specifically in the electricity and gas sector 2011-2015 became a basic sector but 2016-2018 turned into a non-basic. And the results of the Claseen Typology show that there are still 6 relative sectors left behind and 6 potential fast-growing sectors.